Allergic rhinitis: pharmacotherapy in pregnancy and old age. Issue 8 (2nd August 2016) - Ridolo, E.; Caminati, M.; Martignago, I.; Melli, V.; Salvottini, C.; Rossi, O.; Dama, A.; Schiappoli, M.; Bovo, C.; Incorvaia, C.; Senna, G.
ABSTRACT: Introduction : Allergic rhinitis (AR) affects 20-30% of women in reproductive age and may worsen during pregnancy. About 10% of the elderly suffer from AR, and it could be under-diagnosed in these patients. Many drugs are currently available, however AR treatment during pregnancy and old age represents a challenging issue. Areas covered : A review of the literature on the topic has been performed. Expert commentary : In pregnancy, drug avoidance should be carefully balanced with the need for AR optimal control. Topical drugs are suggested as a first approach. The safety and tolerability profile of second-generation antihistamines is well supported. If allergen immunotherapy (AIT) is ongoing and well tolerated, there is no reason for stopping it. AIT initiation in pregnancy is not recommended. For elderly patients, no specific concerns have been highlighted regarding topical treatments, except from nasal decongestionants. Second generation antihistamines are generally well tolerated. Old age should not preclude AIT.